A study on Polycaprolactone coated with Chitosan Microspheres via rapid solvent evaporation - Te, Zi Yang (2019)
Polycaprolactone (PCL) coated with chitosan microspheres (PCL-CH) have a potential to use as mucoadhesive drug delivery system. The size of the microspheres is important for different application in drug delivery system. Therefore, the objective of this study is to prepare the PCL-CH by using different formulation variables such as sodium chloride, concentration of polymer, stirring speed on first emulsion as well as the oil fraction and the effect on the average diameter (davg) of microspheres. The presence of the PCL-CH was determined by using Fourier Transform Infra-Red (FTIR). The davg of the microspheres was characterized by optical microscope. The results show that the davg of PCL-CH increase from 3.53 µm to 3.86 µm when the oil fraction increase from φo = 0.35 to 0.95. The concentration of sodium chloride and the delay condition of sodium chloride affect the davg of microspheres as well. The concentration of polymer increase from 1.2 wt% to 6.0 wt% shows the increase of davg of microspheres and had different davg produced on φo = 0.52 and 0.95. The increase of stirring speed on the first emulsion from 6000 r.p.m to 10 000 r.p.m shows decrease trend of davg on the PCL-CH produced. Thus, it can be concluded that the davg of microspheres was able to influence by the evaluated variables apply depend on different application in mucoadhesive drug delivery system.